The Bivalent Ligand Approach as a Tool for Improving the in vitro Anti‐Alzheimer Multitarget Profile of Dimebon. Issue 8 (3rd July 2013) - Rosini, Michela; Simoni, Elena; Bartolini, Manuela; Soriano, Elena; Marco‐Contelles, José; Andrisano, Vincenza; Monti, Barbara; Windisch, Manfred; Hutter‐Paier, Birgit; McClymont, David W.; Mellor, Ian R.; Bolognesi, Maria Laura
<x xml:space="preserve">Abstract</x> Inspired by the concept of bivalent ligands, we prepared a small set of analogues of the drug candidate dimebon. They were shown to inhibit AChE, Aβ42 aggregation, and NMDA receptor activation to a greater extent than dimebon. Some of these compounds also enhanced the survival of chicken neurons under apoptosis‐inducing conditions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>